Characterization and photodegradation of methylene blue dye using bio-synthesized cerium oxide nanoparticles with Spirulinaplatensis extract - Ali, Mohamed H. H.; Abdelkarim, Mohamad S.; Al-Afify, Afify D. G. (Discover applied sciences, 2024)
Increasing concern about environmental pollution attracts researchers to develop eco-friendly, low-cost, and sustainable approaches for green biosynthesis of nanoparticles to overcome pollutants. This study focuses on the green synthesis of ceria NPs using Spirulina platensis extract as a stabilizing and reducing agent. Characterization measurements, such as optical properties, X-ray diffraction, SEM, TEM, and FT-IR spectroscopy, confirmed the successful synthesis of crystalline and stable ceria NPs with well-defined morphological features. The calculated bandgaps energy of pure ceria, green CeO 2 @Sp 2:1, and CeO 2 @Sp 1:1 were 3.3, 3.15, and 2.94 eV, respectively. The as-synthesized and green ceria NPs showed an excellent degradation efficacy of MB dye under UV irradiation. Furthermore, the green ceria NPs showed high photodegradation efficiency of MB dye (R% = 86.2 and 88.8%) than pure ceria (R% = 76.4%) at certain specific conditions (pH = 11, contact time = 90 min, catalyst dose = 0.3 g/L and MB dye initial concentration = 100 mg/L). The isothermal constants confirmed that the degradation of MB dye is well-fitted with the Freundlich isotherm model (R 2 > 0.99) better than the Langmuir model (R 2 < 0.8). The kinetics models revealed a rapid degradation rate of MB dye, which follows pseudo-second-order models with C e values ranging from 83.33 to 89.29 mg/g, with R 2 > 0.99. These results indicated the potential applicability and promising avenue for developing advanced ceria NPs for wastewater treatment applications. Article highlights Using a novel and facile method to prepare green synthesis ceria NPs using Spirulina platensis extract as a promising photocatalyst. Providing a pioneering approach to preparing green ceria NPs as cheap and eco-friendly photocatalysts for the degradation of MB. Demonstrating the high efficiency of green ceria NPs to eliminate methylene blue (MB) dye using green ceria NPs under UV light exposure.